Handbook of best practice for registrars of final / appellate, regional and international courts and tribunals (Commonwealth Secretariat LondonGB, 2012)
Sets outs recommended best practices for the improvement of non-judicial aspects of court administration, case flow management and court room administration.
Keywords: COURTS